Three new Lepanthes (Orchidaceae: Pleurothallidinae) from south-east Costa Rica - Bogarín, Diego; Karremans, Adam P.; Pupulin, Franco (Lankesteriana: International Journal on Orchidology, 2013)
Three new species of Lepanthes from south-east Costa Rica are described and illustrated. Lepanthes erubescens resembles L. limbellata, from which it can be distinguished by the pendent plants, with inflorescences that borne above the leaf, the upper petal lobe ovate, acute, 1,3 mm wide, larger than the lower lobe, and the ovate lip. Lepanthes sandiorum resembles L. dolabriformis, however it can be distinguished by the smaller plants, the smaller flowers, the narrower petals, which are filiform, with the upper lobe oblong, rounded, entire and glabrous. Lepanthes sanjuanensis is similar to L. elegans, but it is distinguished by the green-purple, un-reticulated leaves, the petals with the upper lobe oblong, rounded, with the margins red, the lower lobe oblong, rounded, divergent at apex, and the pinkish or orange-red lip. Additional comments on the species are provided.